Globalization Drivers and their Impact on Lithuanian Economic Growth and Development - Jatuliavičienė, Gražina; Kučinskienė, Marija (Ekonomika, 2006)
The article offers a discussion focusing on the concept of globalization discussed from different perspectives on the global scale. The fundamental elements of the global business drivers, which identify where domestic, multinational, global companies and countries can benefit most from globalization processes likely to affect the future development perspectives are presented. Special attention is given to understanding globalization as a bundle of processes rather than an end-state. The importance of the Index of Economic Freedom for globalization is discussed on an example of empirical research of the Baltic States, highlighting the Lithuanian positive movements. The current Lithuanian competitive position depends on the capabilities to seize the opportunities offered by globalization and to utilize its core competences in strategic decision-making, leading to the economic development and growth.The methods that were used while preparing the article were analysis of scientific literature, logical analysis of economic indicators, and modeling.